Restorative Justice in Supreme Court Regulations Number 1 of 2024: an Analysis of Islamic Criminal Law Perspective (Case Study of the Garut District Court): Restorative Justice dalam Peraturan Mahkamah Agung Nomor 1 Tahun 2024: Analisis Persfektif Hukum Pidana Islam (Studi Kasus Pengadilan Negeri Garut) - Septiayu, Nadya; Najmudin, Deden; Rozikin, Opik (Al-Jinayah : Jurnal Hukum Pidana Islam, 2026)
Restorative Justice in Supreme Court Regulation Number 1 of 2024 is a concept for resolving criminal cases that prioritizes the restoration of losses for victims. This study aims to analyze its implementation at the Garut District Court and provide an analysis from the perspective of Islamic Criminal Law. This study was conducted using an empirical juridical approach based on interviews, court documents, and a review of literature related to restorative justice and Islamic criminal law. The results of this study indicate that the Garut District Court has successfully implemented restorative justice in the crime of theft. However, in Islamic criminal law, there are differences in concepts that are limited by the rights of Allah and Adam in imposing punishment. This study presents a novel discussion of restorative justice from the perspective of Islamic criminal law, recommending that the two concepts should be integrated according to their provisions and needs, particularly in the context of theft.